1981
DOI: 10.1113/jphysiol.1981.sp013615
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of n‐pentane on the sodium and potassium currents of the squid giant axon.

Abstract: SUMMARY1. Sodium and potassium currents have been recorded in intracellularly perfused squid giant axons before, during and after exposure to solutions of n-pentane in artificial sea water.2. The currents were fitted with equations similar to those proposed by Hodgkin & Huxley (1952) and the changes in the parameters of these equations in the presence of pentane were calculated. 3. In the range of membrane potential -40 to 40 mV, the time constants for activation (tm) and inactivation ('rh) of the Na current,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 11 publications
4
57
1
Order By: Relevance
“…The suppression of 9Na is rather small in relation to the suppression of the peak inward current. The -Na suppression is also similar for the various anaesthetics and resembles that produced by the alcohols and other surface active substances (Haydon & Urban, 1983b) rather than that for the hydrocarbons (Haydon & Kimura, 1981;Haydon & Urban, 1983a). Relative to the hydrocarbons, neither the alcohols nor the present anaesthetics (except perhaps methoxyflurane) seem to produce appreciable thickness increases in membranes.…”
Section: The Hodgkin-huxley Parametersmentioning
confidence: 62%
See 1 more Smart Citation
“…The suppression of 9Na is rather small in relation to the suppression of the peak inward current. The -Na suppression is also similar for the various anaesthetics and resembles that produced by the alcohols and other surface active substances (Haydon & Urban, 1983b) rather than that for the hydrocarbons (Haydon & Kimura, 1981;Haydon & Urban, 1983a). Relative to the hydrocarbons, neither the alcohols nor the present anaesthetics (except perhaps methoxyflurane) seem to produce appreciable thickness increases in membranes.…”
Section: The Hodgkin-huxley Parametersmentioning
confidence: 62%
“…The voltage clamp and data acquisition procedures were as in Kimura & Meves (1979) and the analysis of the sodium currents was as described by Haydon & Kimura (1981). Compensation for the series resistance was applied in all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of non-polar lipophilic substances, comprising a range of straight chain and cyclic hydrocarbons and carbon tetrachloride, on the Na current of the squid giant axon have been described in three earlier papers (Haydon, Requena & Urban, 1980;Haydon &Kimura, 1981 andHaydon &Urban, 1983). It has been shown that these substances affect several of the Hodgkin-Huxley parameters and that the way in which they do so is consistent with their adsorption into the interior of a lipophilic region so causing its expansion in a direction normal to the membrane surface.…”
Section: Dahaydonandb W Urban Introductionmentioning
confidence: 86%
“…Of the other anaesthetics, mentioned at the outset, chloroform and carbon tetrachloride gave results more like those for the hydrocarbons, while the data for ethyl ether had many features in common with the alcohols. Halothane and methoxyflurane occupied central positions.It may be relevant that in their interactions with lipid bilayers, hydrocarbons and alcohols show similarities (membrane fluidity and tension increases) but also differences (hydrocarbons increase thickness whereas alcohols do not) (Colley & Metcalfe, 1972; Ebihara, Hall, MacDonald, McIntosh & Simon, 1979;Elliott & Haydon, 1979; Haydon & Kimura, 1981; and Hodgkin & Huxley (1952), has long been lacking. When the stochastic nature of the gating process is considered, however, it is found that a small change in membrane voltage can mobilize the large existing electrochemical potential difference across the membrane, and thus produce a much greater conductance change than is to be expected from earlier theories (Offner, 1980 In the present experiments, the output of a specially designed low noise voltageclamp amplifier was connected via a 1 Hz-3 KHz window to a low noise differential amplifier with a gain of 1000.…”
mentioning
confidence: 99%
“…It may be relevant that in their interactions with lipid bilayers, hydrocarbons and alcohols show similarities (membrane fluidity and tension increases) but also differences (hydrocarbons increase thickness whereas alcohols do not) (Colley & Metcalfe, 1972;Ebihara, Hall, MacDonald, McIntosh & Simon, 1979;Elliott & Haydon, 1979;Haydon & Kimura, 1981;and …”
mentioning
confidence: 99%